Transcriptome-based characterization of 3’2’-cGAMP signaling mediated immune responses - Yan Gao; Gucheng Xu; Munire Maimaiti; Saihua Chen; Xiang Zhang; Jiameng Hu; Chen Wang; Ze Hong; Haiyang Hu (Computational and Structural Biotechnology Journal)
Cyclic dinucleotides (CDNs) are critical adjuvants in antiviral vaccines and cancer immunotherapy, primarily through the activation of the cGAS-STING signaling pathway. Evaluating the immune responses triggered by CDNs is essential for the development of effective adjuvants. In this study, we performed a comparative transcriptome analysis to characterize the immune responses elicited by the recently identified nuclease-resistant Drosophila and bacterial CDN, 3’2’-cGAMP, in mammalian immune cells. We detected a robust induction of innate immune gene signature following 3’2’-cGAMP stimulation in digitonin-permeabilized mouse primary macrophages, comparable to the response observed with the canonical mammalian CDN, 2’3’-cGAMP. STING deficiency remarkably reduced 3’2’-cGAMP-induced phosphorylation of TBK1 and IRF3 and the induction of IFN-β, indicating that 3’2’-cGAMP signaling-mediated immune responses were mainly STING dependent. In comparison to 2’3’-cGAMP signaling, 3’2’-cGAMP signaling preferentially elicited many STING-dependent genes involved in transcription and nucleosome positioning and assembly in the nucleus, which are likely associated with several enriched pathways, including cellular senescence, HDACs deacetylate histones, and epigenetic regulation of gene expression. The integrative analysis further revealed that 3’2’-cGAMP signaling preferentially induced genes were associated with autoimmune disease-related processes, suggesting a potential side effect that requires monitoring when used as an adjuvant. In conclusion, this study provides the first transcriptional landscape of 3’2’-cGAMP signaling in mammals and reveals the immune response characteristics and potential side effects mediated by 3’2’-cGAMP signaling. These findings may aid in the development of 3’2’-cGAMP-based adjuvants for antiviral vaccines and cancer immunotherapy.